2005
DOI: 10.1177/154405910508401216
|View full text |Cite
|
Sign up to set email alerts
|

Role of TNF-α and Its Receptors in Pericoronitis

Abstract: The classic stimulus for cellular cytokine production is bacterial lipopolysaccharide (endotoxin). It was therefore hypothesized that tumor necrosis factor-alpha (TNF-alpha) may be responsible for pericoronitis. TNF-alpha and its receptors were detected by immunohistochemical staining in third molar pericoronitis in ten patients and ten healthy control samples. The percentage of TNF-alpha positive cells was high in pericoronitis (p = 0.0317). TNF receptors TNF-R1 and TNF-R2 were found in macrophage- and fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
13
1
1
Order By: Relevance
“…The proinflammatory cytokines have also been demonstrated to be able to evoke the bone destructing potential of the HDF's around asymptomatic and clinically innocent looking third molars [8]. This inflammatory reservoir has also suggested being a possible initiator in the transformation into a bone destructive lesion [8]. Our findings supports this only to some extent, since there was no significant difference between the expressions of bone destruction related MMPs between the HDF's and DC's.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The proinflammatory cytokines have also been demonstrated to be able to evoke the bone destructing potential of the HDF's around asymptomatic and clinically innocent looking third molars [8]. This inflammatory reservoir has also suggested being a possible initiator in the transformation into a bone destructive lesion [8]. Our findings supports this only to some extent, since there was no significant difference between the expressions of bone destruction related MMPs between the HDF's and DC's.…”
Section: Discussionsupporting
confidence: 65%
“…This may also have clinical relevance since rationale for symptomless wisdom tooth removal is often justified by radiologic findings and suspected future osteolytic complications; this is not justified based on HDF and DC MMP profiles. Interestingly, it seems that the initiator may be the inflammation itself rather than epithelial remnants of the follicle since it has also been demonstrated that HDF supernatants start to express high levels of MMP-9 if stimulated with TNF-α [8]. However, our new findings suggest that in the case of DC the more bone destructive nature cannot be explained by higher expression of MMPs in the proliferating epithelial interface between cyst and bone leaving the mechanisms to be discovered.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The clinical condition and the progression mechanism of pericoronitis are similar to those of periodontitis. Beklen et al (2005) reported that the transmembrane TNFR1 and R2 were found in macrophage‐ and fibroblast‐like cells, vascular endothelial cells in post‐capillary venules and basal epithelial cells in pericoronitis, but were only weakly expressed in controls. They concluded that TNF‐ α and its receptors may play an important and active role in pericoronitis.…”
Section: Discussionmentioning
confidence: 99%